(untitled) (Research, Society and Development, 2024)
The central objective of this work is to provide a comprehensive analysis of anthropomorphic practices, their motivations and impacts on the physical, behavioral, and emotional well-being of dogs, promoting a deeper understanding of this phenomenon and contributing to the advancement of academic knowledge and awareness of this issue. A systematic review was conducted on the proposed topic, exploring the following databases: PubMed, Science Direct, SciELO, and Google Scholar, using the search terms: "Humanization," "Anthropomorphism," "Anthropomorphization," "Well-being," "Animal," and "Dogs." These same terms were also used in their English translations. The inclusion criteria were: (1) written in Portuguese or English, (2) published between 2014 and 2024, (3) the focus of the research was solely on the canine species, (4) with free access. The exclusion criteria considered: (1) literature reviews and monographs, (2) duplicated articles, or (3) when the objective was other animal species. Thirteen articles were selected. It was observed that 38.46% had a behavioral focus, highlighting separation anxiety (SA) as one of the main psychological aspects; 46.15% focused on nutritional changes, such as obesity and intestinal problems, and 15.38% emphasized the intrinsic effects of humanization on brachycephalic breeds, due to changes from genetic selection. From this analysis, it is concluded that the implications of humanization are multifaceted. The relevance of a deep understanding of the individual characteristics of each species and the integration among veterinarians, guardians, and animals is emphasized as a fundamental pillar to ensure a conducive environment for the health and well-being of dogs.